Student Personnel Services visioning workshop: Proceedings and outputs: October 4, 2010, E201 Enrique Razon Building, DLSU - De Vera, Fritzie Ian P. (Animo Repository, 2010)
As De La Salle University approaches centennial year in 2011, the process of defining the University's vision mission for the next 100 years is among the priorities. There have been various consultations and reflection sessions conducted involving all sectors of the University, which is being spearheaded by new DLSU Chancellor, Br. Ricky Laguda. The Student Personnel Services, through the Directors' Council decided to take part in such reflection initiatives. SPS as a unit will review its past, present, and future directions, and whether these have been or will continue to be responsive to the thrusts and directions of the University. SPS shall conduct the necessary activities to align the unit's VM and objectives with that of DLSU, guided by the The SPS Visioning Process will be carried out in three (3) stages. The first part, Environmental Scanning was started in August. This stage included reflections of the offices, research on trends and practices of student affairs services here and abroad, and economic, political and socio-cultural realities confronting the country at present. The second stage is the SPS Visioning Reflection, where all members of SPS engage in individual and group reflections to come up with keywords that reflect common insights as to the directions and VM of the SPS as a unit. The third and final stage is the Development of the Strategic Objectives - on the SPS and per office levels. This process will be participated by the SPS Directors and 1 Coordinator representative per SPS office. The session last October 4, 2010, served to facilitate the second stage. More than _ participants gathered representing all offices under SPS. The day's activity was facilitated by Ms. Fritzie Ian De Vera, Dean of Student Affairs. The participants were able to reflect individually on their respective roles in SPS, which include the various reasons that inspire them to stay and the contributions they have made to the progress and development of the unit. During the afternoon, presentations on the result of environmental scanning also served as guide to the group reflections on the proposed directions that SPS may undertake and what keywords may form the revised SPS VM.